Teaching Strategies for Language and Literature in Selected High Schools of General Santos City for the Development of TeachTech: Digital Tools for Modern Educators - Torion, Charlyn (International Journal of Arts, Sciences and Education, 2025)
The study was conducted to determine the level of utilization of modern strategies in teaching language and literature in selected high schools of General Santos City. It examined which among digital gamification, interactive PowerPoint presentations, digital classrooms, and non-digital games were frequently or less frequently used by teachers and students. Based on the survey results, it was revealed that certain strategies particularly the digital gamified tools such as Kahoot, Quizziz, Wordwall, Gimkit, Blooket, and Classcraft along with interactive PowerPoint presentations integrating Jamboard and Mentimeter, and digital classroom platforms like Seesaw, Trello, Flipgrid, and Padlet, were not often used due to a lack of familiarity and classroom integration. In response, TeachTech: Digital Tools for Modern Educators was developed as a guide intended to support teachers in incorporating digital strategies into their teaching practices. TeachTech underwent evaluation by administrators and expert teachers to assess its quality. Results showed a high level of validation, particularly in terms of content, design, organization, and readability. Furthermore, an assessment of its acceptability revealed that it was highly received by evaluators. The study highlights the need for broader integration of digital tools in teaching language and literature. TeachTech emerges as a significant initiative to enhance teachers’ competencies in using modern technology in their classrooms.